A high voltage gradient zinc oxide varistor ceramic and its preparation method and application
The high voltage gradient zinc oxide pressure-sensitive ceramics prepared by sintering ZnO, Fe2O3, Li2O and adhesives solve the problem that existing ZnO pressure-sensitive ceramics cannot achieve high voltage gradient characteristics, and achieve high voltage gradient and good aging stability. They are suitable for high voltage transmission and lightning protection applications.
Patent Information
- Application Number
- CN202410776323.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-06-17
AI Technical Summary
Existing ZnO voltage-sensitive ceramics cannot achieve high voltage gradient characteristics, and it is difficult to meet the protection needs of lightning arresters on unmanned platforms such as ultra-high voltage AC and DC transmission and offshore wind power.
By using ZnO, Fe2O3, Li2O and adhesive as raw materials and prepared by high-temperature sintering, the molar ratio of Fe2O3 and Li2O is (1.06-1): 1, and the total molar sum of Fe2O3 and Li2O accounts for 10-40% of the moles of zinc oxide. The oxygen vacancies defects in ZnO are suppressed by Fe3+ ions and Li+ ions, forming defective dipole structures and pinning phases, and improving the voltage gradient of the ceramic.
ZnO voltage-sensitive ceramics with high voltage gradient have a simple component number, a voltage gradient can be adjusted, and have good aging stability. They are suitable for lightning arresters for ultra-high voltage transmission, electronic devices overvoltage protection or lightning protection devices.
Smart Images

Figure CN118754641B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high voltage gradient zinc oxide varistor ceramic and a preparation method and application thereof, belonging to the technical field of functional varistor ceramic and preparation thereof. Background Art
[0002] Lightning arresters are important devices used in power systems to protect equipment from lightning and grid overvoltage damage. Zinc oxide varistors are the core materials in modern lightning arresters. They are widely used because of their excellent nonlinear volt-ampere characteristics and high voltage gradient. Their nonlinear characteristics and varistor voltage gradient determine the protection level of the arrester. The nonlinear coefficient of pure ZnO ceramics is very small and has almost no nonlinear characteristics. In order to improve the nonlinear volt-ampere characteristics of ZnO ceramics, multiple oxides (Bi2O3, Sb2O3, Co3O4, Cr2O3, MnO2, etc.) are usually used in combination with ZnO to prepare multi-component ZnO varistor ceramics. During the sintering process of ZnO ceramics, multiple oxide components are precipitated at the grain boundaries to construct grain boundary barrier layers, inducing the nonlinear resistance characteristics of ZnO ceramics. However, in order to achieve the improvement of the varistor performance of multi-component ZnO ceramics, it is necessary to increase the types and contents of oxides in the system, which makes it easy for multiple oxides to react during preparation and the varistor performance is difficult to control. The performance improvement of ZnO varistor ceramics based on this mechanism has gradually approached a bottleneck. With the rapid development of UHV AC / DC transmission and unmanned platforms such as offshore wind power, higher requirements are placed on the protection level of lightning arresters. Therefore, it is urgent to develop ZnO varistor ceramics with high voltage gradient. Summary of the invention
[0003] Aiming at the problem that the existing ZnO varistor ceramics cannot realize high voltage gradient characteristics, the present invention provides a high voltage gradient zinc oxide varistor ceramic and a preparation method and application thereof.
[0004] The technical solution of the present invention:
[0005] One of the purposes of the present invention is to provide a high voltage gradient zinc oxide varistor ceramic, which is specifically made of ZnO, Fe2O3, Li2O and an adhesive as raw materials and is sintered at a high temperature.
[0006] It is further defined that the total molar amount of Fe2O3 and Li2O accounts for 10-40% of the molar amount of zinc oxide.
[0007] It is further defined that the molar ratio of Fe2O3 to Li2O is (1.06-1):1.
[0008] It is further defined that the binder is a PVA aqueous solution with a volume fraction of 5vt% and a PVA molecular weight of 10,000.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned high voltage gradient zinc oxide varistor ceramic, which specifically comprises the following steps:
[0010] (1) ZnO, Fe2O3 and Li2O are dispersed in anhydrous ethanol, mixed evenly by ball milling, and the obtained mixed powder is dried and sintered at high temperature to obtain pre-burned powder;
[0011] (2) The pre-fired powder obtained in (1) is mixed with a binder, dried, pressed into a prefabricated block, and sintered again at a high temperature to obtain a high voltage gradient zinc oxide varistor ceramic.
[0012] It is further defined that the amount of anhydrous ethanol used in (1) is 5-5.2 times the total mass of ZnO, Fe2O3 and Li2O.
[0013] It is further defined that the ball milling conditions in (1) are: a rotation speed of 300 rad / min, a forward and reverse cycle period of 1 h, a ball milling time of 12 h, and a temperature of 20-30°C.
[0014] It is further defined that the drying temperature in (1) is 60-80° C. and the drying time is 5-8 h.
[0015] It is further defined that (1) the medium-high temperature sintering conditions are: raising the temperature from 50°C to 800°C at a rate of 10°C / min and keeping the temperature for 2 h.
[0016] It is further defined that the amount of the binder in (2) is 50% of the mass of the pre-burnt powder.
[0017] It is further defined that the mixing speed in (2) is 300 rad / min and the mixing time is 12 h.
[0018] It is further defined that the drying temperature in (2) is 80° C. and the drying time is 5 to 8 hours.
[0019] It is further defined that the pressing conditions in (2) are: cold pressing at room temperature under atmospheric pressure for 8-10 min, and the pressure is 10 MPa.
[0020] It is further defined that (2) the medium-high temperature sintering conditions are: raising the temperature from 50°C to 1100°C at a rate of 10°C / min, keeping it at that temperature for 1 h, continuing to raise the temperature to 1150-1250°C at a rate of 10°C / min, keeping it at that temperature for 2.5 h, and finally cooling it to room temperature at a rate of 10-15°C / min.
[0021] The third object of the present invention is to provide an application of the above-mentioned high voltage gradient zinc oxide varistor ceramic, specifically for use in lightning arresters for ultra-high voltage power transmission, overvoltage protection of electronic devices or lightning protection devices.
[0022] Beneficial effects:
[0023] The present invention uses Fe2O3, Li2O and ZnO for compounding, while ensuring the minimum number of components of ZnO varistor ceramics, comprehensively utilizes grain resistance and grain boundary barrier layer to induce and improve ZnO ceramic varistor characteristics, and obtains high voltage gradient ZnO varistor ceramics. Compared with the prior art, the present invention also has the following advantages:
[0024] (1) The present invention utilizes Fe 3+ Ions and Li + Ions can suppress the concentration of oxygen vacancy defects in ZnO and increase grain resistance. 3+ Ions and Li + ions to achieve Fe 3+ Ions and Li + The high content of ions is completely dissolved into the ZnO lattice and tends to enter the same lattice to form a defect dipole structure. This structure captures and scatters electrons, making the modified ZnO ceramics have varistor properties. 3+ When the addition amount is higher (higher than 10 mol%), it precipitates at the grain boundary to form a pinning phase, which inhibits grain growth, increases the grain boundary content, and further increases the voltage gradient.
[0025] (2) The high voltage gradient ZnO varistor ceramic provided by the present invention has a simple number of components. By adjusting the addition amounts of Fe2O3 and Li2O, the effective regulation of the doped ceramic varistor voltage can be achieved to obtain a high voltage gradient ZnO varistor ceramic.
[0026] (3) The zinc oxide-based ceramics prepared by the present invention have a high voltage gradient, and the voltage gradient is controllable and has good aging stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD spectra of zinc oxide-based ceramic materials obtained in different embodiments and comparative examples at room temperature;
[0028] Figure 2 for Figure 1 A partial enlarged view of
[0029] Figure 3 is the lattice constant of the zinc oxide-based ceramic materials obtained in different embodiments and comparative examples;
[0030] Figure 4 The SEM photos of zinc oxide-based ceramic materials obtained in different embodiments and comparative examples;
[0031] Figure 5 The volt-ampere characteristic (EJ) curves of the zinc oxide-based ceramic materials obtained in Examples 1 to 4 and Comparative Example 5;
[0032] Figure 6 The volt-ampere characteristic (EJ) curves of the zinc oxide-based ceramic materials obtained in Comparative Examples 1 to 4 are shown. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0037] Example 1
[0038] Disperse zinc oxide, Fe2O3 and Li2O in an ethanol solvent, wherein the molar ratio of Fe2O3 to Li2O is 1:1, and the total molar amount of Fe2O3 and Li2O accounts for 10% of the molar amount of zinc oxide. The amount of anhydrous ethanol is 5 times the total mass of the inorganic matter. Mix by planetary ball milling at room temperature for 12 hours, and mix evenly according to the process of rotating speed of 300 rad / min and forward and reverse cycle period of 1 hour;
[0039] Keep the temperature at 80℃ for 4 hours, dry the mixed powder, and use the furnace temperature control program to increase the temperature from room temperature to 800℃ at a rate of 5℃ / min, and sinter for 2 hours to obtain pre-burned powder;
[0040] The pre-burned powder and the binder are pre-mixed using a mixer, the pre-mixing speed is 40rad / min, and the time is 10min; then the binder and the pre-burned powder are fully mixed using a high-speed flying knife mixer, the barrel speed is 16rad / min, the flying knife speed is 1400rad / min, and the mixing time is 1.5h; after obtaining the powder, it is dried at 60℃ for 8h. The binder is a PVA aqueous solution with a volume fraction of 5vt%, the PVA molecular weight is 10000, and its amount is 50% of the mass of the pre-burned powder. The prefabricated block was obtained by cold pressing at room temperature under vacuum for 10 min, with a pressure of 15 MPa and a vacuum degree of 0.095 MPa. The prefabricated block was placed in a high-temperature furnace, heated from 50°C to 600°C, and kept warm for 0.5 h. The temperature was further heated to 1100°C and kept warm for 2 h, and then heated to 1250°C and kept warm for 4 h. The heating rate was 5°C / min. After the end of the heat preservation, the temperature was lowered to room temperature at a rate of 5°C / min to obtain a zinc oxide-based ceramic material named (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.1.
[0041] Example 2
[0042] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 20% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.2.
[0043] Example 3
[0044] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 30% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.3.
[0045] Example 4
[0046] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 40% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.4.
[0047] Comparative Example 1
[0048] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 2% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.02.
[0049] Comparative Example 2
[0050] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 1.5% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.015.
[0051] Comparative Example 3
[0052] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 1% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.01.
[0053] Comparative Example 4
[0054] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 0.5% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.005.
[0055] Comparative Example 5
[0056] The difference between this embodiment and embodiment 1 is that the total molar amount of Fe2O3 and Li2O accounts for 0% of the molar amount of zinc oxide, and the remaining process steps and parameter settings are the same as those in embodiment 1 to obtain a zinc oxide-based ceramic material, (Fe 0.5 Li 0.5 ) x Zn 1-x O, x is 0.
[0057] Effect example
[0058] (1) XRD spectra of zinc oxide-based ceramic materials obtained in different embodiments and comparative examples at room temperature are as follows: Figure 1 As shown in the figure, the diffraction peak of zinc oxide-based ceramic material corresponds to the peak position of ZnO standard card (JCPDS36-1451), indicating that the main crystalline phase of the ceramic is ZnO. 3+ -Li + When the addition amount x≤2mol%, there is no diffraction peak of other phases in the XRD spectrum of ZFL ceramics. 3+ -Li + After that, when x ≥ 10 mol%, a secondary phase appeared. After analysis by Jade software, it was found that the precipitated secondary phase was ZeFe2O3 (spinel phase). This indicates that Fe 3+ -Li + At a higher doping level, Li + and Fe 3+ It cannot be completely dissolved in the ZnO lattice, and some Fe 3+ The ions precipitate to form a second phase. No Li + The reason is that at the sintering temperature of 1250℃, ZnO and Li2O are not easy to react to form other phases without other additives.
[0059] The XRD spectrum in the range of 34°-37° is further enlarged and analyzed, such as Figure 2 As shown by Figure 2 It can be seen that as the doping amount increases from 0mol% to 1mol%, the diffraction peak (101) moves to a higher diffraction angle. But the range of movement is not large. When the doping amount increases from 10mol% to 40mol%, the (101) crystal plane diffraction peak representing ZnO moves significantly to the right compared to the diffraction peak of single-phase ZnO, but the diffraction peak does not move significantly as the addition amount increases. According to the Bragg equation, it can be seen that the movement of the diffraction peak is due to the change in the lattice constant. Due to Fe 3+ -Li + Entering the ZnO lattice will cause the lattice to shrink, thus causing the diffraction peak to move to a higher angle. Therefore, the diffraction peak of the ceramic is biased to the right. When x ≥ 10 mol%, the diffraction peak (101) does not move significantly, and the diffraction peak of the spinel phase gradually increases. Analysis shows that Fe 3+ -Li + It cannot be completely dissolved into the ZnO grains and reacts with ZnO to form spinel phase. The XRD spectrum data of the fine-scanned ceramic is put into Jade. After optimizing the XRD data, the lattice constant of the ZnO grains in the ceramic sample can be calculated, such as Figure 3 As shown. Figure 3 It can be seen that with the increase of Fe 3+-Li + As the doping amount increases, the lattice constant of ZnO grains gradually decreases, which is mainly due to the 3+ Ions and Li + The ions are dissolved into the ZnO lattice, and the average radius of the two ions is smaller than that of the Zn ions. When the two ions tend to replace two adjacent Zn ions, the lattice plane spacing will decrease, thereby reducing the lattice constant of the modified ceramic.
[0060] (2) SEM photos of zinc oxide-based ceramic materials obtained in different embodiments and comparative examples are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that adding Fe 3+ -Li + The ceramics modified by Fe ions have obvious differences in grain size compared with the single-phase ZnO ceramics. 3+ -Li + The increase of Fe ion content significantly increases the grain size. When the addition amount reaches 10mol%, the grain size decreases significantly, and the grain boundary content increases. And when x = 10mol% to 40mol%, a large amount of second phase precipitation can be seen at the grain boundary, which corresponds to the XRD spectrum analysis results. This shows that at high additions, some Fe 3+ Ions cannot dissolve into the ZnO lattice, and the Fe 3+ Ions and Zn 2+ ions react to form spinel phase. 3+ -Li + The addition of ions will restrict the growth of ZnO grains and generate a second phase.
[0061] (3) The volt-ampere characteristic (EJ) curves of the zinc oxide-based ceramic materials obtained in different embodiments and comparative examples are shown in FIG. Figure 5 and Figure 6 As shown in the figure, except for the sample with doping amount x=0mol%, all other samples show obvious nonlinearity. And with the increase of doping amount, the voltage gradient of the sample changes, and when the doping amount increases to x≥10mol%, the voltage gradient of the sample is greatly improved.
[0062] according to Figure 5 and 6 The corresponding performance parameters are calculated and the results are shown in Table 1 below:
[0063] Table 1
[0064]
[0065] From the above table, we can see that the varistor voltage gradient E of the low-doped ceramic sample is 1mAIn the range of x = 0 mol% - 2 mol%, as Fe 3+ -Li + The amount of addition increases first and then decreases, reaching a maximum of 23.77V / mm when x=1mol%, and the leakage current J L Reached a minimum value of 0.0319mA / cm 2 The nonlinear coefficient α also increases first and then decreases with the increase of the addition amount, reaching a maximum value of 25.27 when x = 1 mol%. This shows that the proper addition of Fe2O3 and Li2O can improve the insulation of the modified ceramic and reduce the leakage current density. 3+ Ions and Li + The defect dipole structure formed by ions can capture scattered electrons, making the modified ceramics have varistor properties and improving the voltage gradient of the ceramic samples. 1mA In the range of x = 10 mol%-40 mol%, as Fe 3+ -Li + The content of the catalyst decreases slightly, and reaches a maximum value of 1422.09 V / mm when x=10 mol%. L With the increase of the addition amount, it first increases and then decreases, and reaches the minimum value of 1.5582 mA / cm when x = 30 mol%. 2 At the same time, α first increases and then decreases with the increase of the addition amount, reaching a maximum value of 10.74 when x = 30 mol%.
[0066] Through the analysis of the lattice constant and micromorphology of ceramics with different doping amounts, it is known that under appropriate Fe 3+ -Li + ions, Fe 3+ Ions and Li + Ions can dissolve into the ZnO lattice, replace Zn ions, and tend to enter the same lattice to form a defect dipole structure. The formation of this defect structure can inhibit the generation of Zn interstitial ions and oxygen vacancies, thereby increasing the resistance of ZnO grains and improving the insulation of ZnO ceramics. In addition, the scattering and capture of carriers by the defect dipole structure makes the resistance of the modified ZnO ceramics have nonlinear characteristics under a certain electric field. When Fe 3+ -Li + When the ion content is high, some Fe 3+ The ions precipitate at the grain boundaries in the form of spinel phase, which not only further increases the content of grain boundaries, but also increases the grain boundary resistance. At this time, the modified ZnO ceramics have both defect dipoles and grain boundary Schottky barriers, which makes the modified ZnO ceramics with high addition have high voltage gradient and low leakage current density.
[0067] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A high voltage gradient zinc oxide varistor ceramic, characterized in that: Made of ZnO, Fe2O3, Li2O and adhesive as raw materials, it is sintered at high temperature; The total molar amount of Fe2O3 and Li2O accounts for 10-40% of the molar amount of zinc oxide; The molar ratio of Fe2O3 and Li2O is (1.06~1):
1.
2. The high voltage gradient zinc oxide varistor ceramic according to claim 1, characterized in that: The binder is a PVA aqueous solution with a volume fraction of 5vt% and a PVA molecular weight of 10,000.
3. A method for preparing the high voltage gradient zinc oxide varistor ceramic according to any one of claims 1 to 2, characterized in that: include: (1) ZnO, Fe2O3 and Li2O are dispersed in anhydrous ethanol, mixed evenly by ball milling, and the obtained mixed powder is dried and sintered at high temperature to obtain pre-burned powder; (2) The pre-fired powder obtained in (1) is mixed with a binder, dried, pressed into a prefabricated block, and sintered again at a high temperature to obtain a high voltage gradient zinc oxide varistor ceramic.
4. The preparation method according to claim 3, characterized in that: (1) The amount of anhydrous ethanol used is 5-5.2 times the total mass of ZnO, Fe2O3 and Li2O; the ball milling conditions are: rotation speed of 300 rad / min, forward and reverse cycle period of 1 h, ball milling time of 12 h, and temperature of 20-30°C.
5. The preparation method according to claim 3, characterized in that: (1) The drying temperature is 60-80°C for 5-8 hours; the high temperature sintering conditions are: raising the temperature from 50°C to 800°C at a rate of 10°C / min and keeping it at that temperature for 2 hours.
6. The preparation method according to claim 3, characterized in that: (2) The amount of binder used is 50% of the mass of the pre-burnt powder; the mixing speed is 300 rad / min, the time is 12 h; the drying temperature is 80° C., and the time is 5 to 8 h.
7. The preparation method according to claim 3, characterized in that: (2) Medium pressing conditions are: cold pressing at room temperature under atmospheric pressure for 8-10 min, with a pressure of 10 MPa; high temperature sintering conditions are: heating from 50°C to 1100°C at a rate of 10°C / min, keeping warm for 1 h, then heating to 1150-1250°C at a rate of 10°C / min, keeping warm for 2.5 h, and finally cooling to room temperature at a rate of 10-15°C / min.
8. An application of the high voltage gradient zinc oxide varistor ceramic according to any one of claims 1 to 2, characterized in that: Used in lightning arresters for UHV power transmission, overvoltage protection for electronic devices or lightning protection devices.
Citation Information
Patent Citations
Zinc oxide ceramic with adjustable nonlinear coefficient as well as preparation method and application of zinc oxide ceramic
CN118084479A
Process for producing zinc oxide varistor
US20100117271A1
Process for producing zinc oxide varistor having high potential gradient and high non-linearity coefficient
US20130133183A1